2017
DOI: 10.1016/j.jsams.2016.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Exercise and Sports Science Australia (ESSA) position statement on exercise prescription for the prevention and management of osteoporosis

Abstract: Specific guidelines for safe and effective exercise for bone health are presented. Individual exercise prescription must take into account existing bone health status, co-morbidities, and functional or clinical risk factors for falls and fracture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
226
0
25

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 259 publications
(268 citation statements)
references
References 75 publications
(82 reference statements)
2
226
0
25
Order By: Relevance
“…These results are consistent with previous studies that found benefits of impact exercises on bone health. 14,37 We noted that the effects of exercise dose on bone mineral density were significantly greater among women who were not using osteoporosis medication. Therefore, women with established osteoporosis did not show an added benefit of greater exercise volume on bone mineral density.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…These results are consistent with previous studies that found benefits of impact exercises on bone health. 14,37 We noted that the effects of exercise dose on bone mineral density were significantly greater among women who were not using osteoporosis medication. Therefore, women with established osteoporosis did not show an added benefit of greater exercise volume on bone mineral density.…”
Section: Discussionmentioning
confidence: 92%
“…Indeed, our exploratory analysis revealed that greater improvements in bone mineral density were seen in women who reported completing a greater amount of impact exercises. These results are consistent with previous studies that found benefits of impact exercises on bone health …”
Section: Discussionmentioning
confidence: 99%
“…Not only do EAS help maintain the body's fitness as well as physical health, but they also improve mood, self-esteem, and social skills [15,16]. The activities are proven to have preventive effects among healthy individuals and treatment effects among patients of various illnesses [17][18][19]. EAS are beneficial to those with hypertension; they reduce the risk of obesity, heart disease, diabetes, and colon cancer; they lower premature mortality rates; and they enhance osteoarthritis function in older people [18,[20][21][22].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Nahiz eta hezurraren egokitze positiboa sustatzeko bizitza osoan zehar egin beharreko ariketa fisikoaren «dosia» orain arte zehaztua izan ez den arren, ariketa fisikoak hezurrean duen eragina jarduera fisiko motaren, kantitatearen eta intentsitatearen menpe egongo da [31].…”
Section: Ariketa Fisikoaren Eragina Hezur-dentsitateanunclassified